(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2020)
Background: Among the recovery phases, patient achieve their cognitive and psychomotor skills in intermediate phase. Rapid clearance drug like Sevoflurane has beneficial effect on early cognitive recovery which allows early mobilization and reduce post operative complication but Halothane with delayed recovery profile is still commonly used in our country. Objective: So the study was done to compare the post operative cognitive recovery in adult patients receiving sevoflurane and halothane anaesthesia and with a view to increase the use of sevoflurane over halothane. Settings and study design: This prospective randomized comparative study was done in Anaesthesia, analgesia and intensive care medicine department of BSMMU Hospital between September 2009 to June 2011. A total 60 patients[30 in sevoflurane group (Group-S) and 30 in halothane group(Group-H)]of either sex, 18-50 years, ASA-I and II, elective surgery under general anaesthesia, lasting more than 1 hour and remaining 24 hours after surgery were the study population. Cognitive recovery was assessed using Bangla adaptation mini-mental state examination (BAMSE) and paper pencil test-Trail making test part- A (TMT-A) one day prior to surgery (baseline value) and 30 minutes after recovery then at hourly interval up to 3.5 hours postoperatively and compared. Results: Emergence time was significantly shorter in Group-S compared to Group-H (10.85 min & 15.13 min respectively, P<0.001). The mean BAMSE score Group-S was 29 at baseline and demonstrated no change at the end of the observation, while the Group-H experienced a fall and rise in BAMSE score. Time taken by the patients of Group-S to complete (TMT-A) at 30 minutes after recovery was significantly less (40.9 sec. Vs 55.8 sec, P <0.001) than patients of Group-H. And no significant difference was observed between groups at 1.5 hrs, 2.5 hrs and 3.5 hrs. Conclusion: So the study concludes that adult patient of sevoflurane group experienced an early post operative cognitive recovery than halothane group. Though sevoflurane is costly, considering the benefits of patients in terms of early cognitive recovery that causes less postoperative complications and shorter hospital stay, sevoflurane should be used instead of halothane Journal of Bangladesh Society of Anaesthesiologists 2015; 28(1): 5-11